Análise das propriedades físico-químicas de peptídeos não-citotóxicos para macrófagos raw 264.7 - Juliana Rodrigues Moraes (2023)
Bioactive peptides, whether of natural or synthetic origin, perform various biological functions, including antimicrobial and immunomodulatory activities. Their physicochemical properties, such as charge, structure, and hydrophobicity, influence their biological effects. Imbalance in these attributes can lead to cytotoxicity to host cells, which is undesirable for therapeutic applications. Because of this, the aim of this work was to determine which physicochemical attributes of bioactive peptides are responsible for their cytotoxic activity in a murine macrophage model. Twenty bioactive peptides were synthesized through Fmoc solid-phase synthesis, purified by liquid chromatography, and identified byMALDI- ToF mass spectrometry. The physicochemical properties of the peptides were determined using the enCrypted program, and the results were subjected to the K- Means clustering algorithm. The peptides were classified into four distinct groups, as evidenced by Principal Component Analysis (PCA). Loadings analysis and the ANOVA statistical test were applied to identify the physicochemical properties that contributed most to the groups formation, which included volume and monoisotopic mass, secondary structure coefficients, solvent accessibility of residues, and the percentage of basic and charged residues. MTT assays revealed that Group 0 includes non-cytotoxic peptides. Groups 1, 2, and 3, on the other hand, contain peptides with confirmed cytotoxicity in this study (LyeTx1, D and L- ecPis2s) and in other articles, suggesting that the above-mentioned physicochemical properties are responsible for the separation between toxic and non-toxic peptides. As for the quantification of nitric oxide, it was observed that the peptides LyeTx1, D-ecPis2s, L-ecPis2s, L-Phes, Lun1 F12A, and Schisn3 decreased NO concentration, while the peptide Lun1 K7A increased it. The relation between physicochemical attributes and the immunomodulatory activity of these peptides requires further investigation. In conclusion, in this study, we determined physicochemical characteristics that appear to be crucial in determining the non- cytotoxicity of a bioactive peptide. Furthermore, we suggest that these attributes should be considered in the design of new non-cytotoxic peptides.